Examining Mothers' Childhood Maltreatment History, Parental Reflective Functioning, and the Long-Term Effects of the Minding the Baby® Home Visiting Intervention. (August 2022) - Condon, Eileen M.; Tobon, Amalia Londono; Holland, Margaret L.; Slade, Arietta; Mayes, Linda; Sadler, Lois S.
Research is needed to better understand how childhood maltreatment history affects parental reflective capacities, and whether early childhood interventions help mitigate these effects. We examined associations between childhood maltreatment and current parenting (parental reflective functioning, parenting behaviors) among mothers who participated in a follow-up study ( N = 97) of the Minding the Baby ® (MTB) randomized control trial. MTB is a home visiting program that aims to help mothers understand their child's mental states (feelings, intentions, needs) by promoting parental reflective functioning. Mothers retrospectively reported childhood maltreatment using the Childhood Trauma Questionnaire. Endorsing a higher number of childhood maltreatment subtypes was associated with less supportive/engaged parenting and higher pre-mentalizing modes, or difficulty with appropriately reflecting on the child's mental states. These relationships were not moderated by participation in the MTB intervention. However, exploratory analyses of individual maltreatment subtypes revealed that participation in MTB may mitigate the harmful effects of childhood emotional abuse on pre-mentalizing modes, specifically. Further research is needed to understand the mechanisms through which early childhood interventions may prevent intergenerational cycles of maltreatment.